2014
DOI: 10.1134/s0026261714050154
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition of the activated sludge of Moscow wastewater treatment plants

Abstract: The contribution of the major technologically important microbial groups (ammonium and nitrite oxidizing, phosphate accumulating, foam inducing, and anammox bacteria, as well as plancto mycetes and methanogenic archaea) was characterized for the aeration tanks of the Moscow wastewater treatment facilities. FISH investigation revealed that aerobic sludge were eubacterial communi ties; the metabolically active archaea contributed insignificantly. Stage II nitrifying microorganisms and planctomycetes were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Our study also found other important and potential groups that are observed in polluted environments. Thus, Chloroflexi was found in sites with the application of activated sludge from the wastewater treatment industry 33 , and Anaerolinea was found in sites contaminated with petroleum 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found other important and potential groups that are observed in polluted environments. Thus, Chloroflexi was found in sites with the application of activated sludge from the wastewater treatment industry 33 , and Anaerolinea was found in sites contaminated with petroleum 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Violation of internal dynamic equilibrium in sludge ecosystem promotes the active sludge foaming process which increases the sludge index. In global experience, filamentary foaming of activated sludge (existence of filamentary microorganisms) is a widely known problem of the biological treatment of wastewater [Kallistova et al 2014; Nastro, Gambino 2017]. Filamentary microorganisms include bacteria and fungi.…”
Section: Related Workmentioning
confidence: 99%
“…Considering that sludge represents approximately 5% of the total residues produced by the winery (Bharathiraja et al, 2020), the composting of grape stalks, pomace and sludge rich in nitrogen has also been used to reduce operational costs (Bertran et al, 2004;Bustamante et al, 2007Bustamante et al, , 2009. Winery sludge is an alkaline and highly humid substrate with a high amount of nitrogen and an elevated number of microorganisms (Pascual et al, 2018), including Proteobacteria, Bacteroidetes, Firmicutes, Nitrospira, Dechloromonas, Arcobacter, Nitrobacter, Planctomycetes, Chloro exi, and several microorganisms that participate in the nitrogen cycle (Gao et al, 2016;Kallistova et al, 2014;Neklyudov et al, 2008) . These phylogenetic groups have also been reported in the early stages of compost, suggesting that sludge could be a suitable supplement for the composting process of winery residues, improving the conditions of the process, increasing bene cial microorganisms, and reducing sludge management costs.…”
Section: Introductionmentioning
confidence: 99%